2019
DOI: 10.3390/en12214108
|View full text |Cite
|
Sign up to set email alerts
|

Air-Floating Characteristics of Large-Diameter Multi-Bucket Foundation for Offshore Wind Turbines

Abstract: In the present study, as a novel and alternative form of foundation for offshore wind turbines, the air-floating characteristics of a large-diameter multi-bucket foundation (LDMBF) in still water and regular waves are investigated. Following the theory of single degree of freedom (DOF)-damped vibration, the equations of oscillating motion for LDMBF are established. The spring or restoring coefficients in heaving, rolling and pitching motion are modified by a dimensionless parameter ϑ related to air compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It was observed that the natural period of this structure increases with the draft, and when the wave period is close to the natural period, the foundation experiences a large dynamic response. Liu and Zhang et al [41] established equations for the oscillating motion of an AFMBF and conducted model tests with varying drafts and spacing between buckets in shallow water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the natural period of this structure increases with the draft, and when the wave period is close to the natural period, the foundation experiences a large dynamic response. Liu and Zhang et al [41] established equations for the oscillating motion of an AFMBF and conducted model tests with varying drafts and spacing between buckets in shallow water.…”
Section: Introductionmentioning
confidence: 99%
“…The studies mentioned above focused on the stability and motion characteristics of various structures, including box-type air-floating structures with different compartments, single bucket foundations with multiple subdivisions, and multi-bucket foundations. On the one hand, previous studies have been conducted on the motion responses of multibucket foundations in shallow water [41]. However, these studies were limited by the use of elastic ropes to restrict the in-plane motion of the structure during testing.…”
Section: Introductionmentioning
confidence: 99%
“…Since the elastic stiffness of the air spring is smaller than that of the water spring, the resistance of the floating body with an air cushion is less than the resistance of the ordinary floating body with the same draft. As a result, the stability of the floating body with an air cushion may be less than that of the ordinary floating body [32][33][34]. In the towing process, in addition to paying attention to the motion response of the structure, the emphasis should also be placed on the air cushion and the interaction forces' response.…”
Section: Introductionmentioning
confidence: 99%
“…Their focus was the motions of CBF which just needs initial stability properties. Liu et al [20][21] studied a similar air cushion structure to that in [17], and gave only the properties of initial stability. Chenu at al.…”
Section: Introductionmentioning
confidence: 99%